Fall cover crop nitrogen uptake drives reductions in winter‐spring leaching. Issue 3 (6th April 2022) - Sedghi, Nathan; Weil, Ray
Abstract: Cover crops can reduce nitrate leaching after cash crop harvest. Despite widespread cover crop implementation, there has been a limited effect on water quality in the Chesapeake Bay watershed. We hypothesize that typical timing for Maryland cover crop planting after cash crop harvest is too late to allow roots to take up substantial nitrate from the soil profile before it is leached by winter drainage water. Across four site‐years (including sandy and silty soils), we compared various planting dates for a radish ( Raphanus sativus L.)–crimson clover ( Trifolium incarnatum L.)–triticale ( Triticosecale ) cover crop mixture. Also, across two site‐years we compared early‐planted pure rye, radish, and a three‐species mixture with no cover. We measured cover crop biomass and N content and used tension lysimeters to measure deep soil porewater nitrate concentrations. Cumulative nitrate leaching was calculated from these concentrations and weather‐based drainage estimates. Cover crops were planted on four dates over a 6‐wk period. Overall, cover crops planted first, second, third, fourth, and no cover crop (just weeds) resulted in 3, 340, 3, 160, 1, 600, 303, and 164 kg ha −1 of biomass; biomass N accumulation of 65.5, 68.6, 44.0, 9.88, and 4.79 kg N ha −1 ; and mean porewater concentrations of 2.71, 2.57, 4.72, 10.0, 17.1 mg L −1 of nitrate‐N, respectively. Over two site‐years, the three‐species mix performed as well or better than pure rye or radish. Early planting altered cover crop species proportions, increased cover crop productivity, and reduced nitrate leaching from agricultural fields. Core Ideas: Earlier‐planted cover crops took up more nitrogen in fall than later‐planted cover crops. Earlier planting of radish–clover–grass cover mix increased radish proportion in fall biomass. The mass of nitrate leached from plots planted in early October was 2–4 times greater than earlier‐planted covers. Fall cover crop nitrogen uptake was closely and negatively related to mass of nitrate leached during winter and spring.